Granulomatosis with Polyangiitis: A Case of Nasal Mass, Necrotic Lung, and Normal Kidneys - Spanuchart, Ittikorn (Hawaii J Med Public Health, 2015)
A diagnosis of granulomatosis with polyangiitis (GPA) can be challenging given various clinical manifestations. We report an incident case of GPA presenting with chronic sinusitis and mimicking an early lung abscess without renal involvement. A 51 year-old woman with chronic obstructive sinusitis presented with subacute dyspnea, pleuritic chest pain and fever. Physical examination revealed a right nasal mass without discharge or bleeding. Decreased to absent breath sounds and dullness to percussion were noted at the left lung base. Laboratory findings were significant for leukocytosis but normal renal function. The chest CT demonstrated dense consolidation with hypo-enhancement of the lingula. The sinus CT revealed an enhancing mass in the right nasal cavity and anterior ethmoid sinuses with associated bony destruction. Patient did not improve with empiric antibiotics for lung abscess. Aspiration of the lingular fluid showed purulent material, however, microbes did not grow in culture. A positive C-ANCA screen was confirmed. A right nasal biopsy was performed which revealed granulomatous inflammation with focal necrosis and vasculitis. The final diagnosis was GPA. Given various clinical manifestations, the diagnosis of GPA can be difficult to distinguish from infectious etiologies. This can delay the treatment, which may be life-saving and organ sparing. We emphasize that an initial screening ANCA serology test is recommended in patients with suggestive clinical findings of GPA. Biopsy of an affected organ is paramount for the definitive diagnosis.